School Based Development Of Scout Teachings - Paulus Rahadi Pawitra; Trinovandhi Setyawan (IKIP Budi Utomo Malang, 2020)
This development aims to produce a product of a scout textbook as’part’of an’effort to’create’a fun and active learning process. This study uses a model of floating (Research and development) from Brog and Gall (in Winarno) includes the following stages: 1. Data collection, 2. Planning, 3. Developing products, 4. Small group testing, 5. Revision of the 1st product , 6. Large group test, 7. Revision of the second product, 8. Field testing, 9. Revision of the 3rd program, 10. Dissemination and implementation. The instruments are interviews and questionnaires. Quantitative and descriptive data analysis techniques